ISLAMIC RELIGIOUS EDUCATION AS AN INSTRUMENT FOR PREVENTING SEXUAL VIOLENCE IN EDUCATIONAL INSTITUTIONS: A LEGAL AND CHARACTER EDUCATION PERSPECTIVE - Ramadhan, Muhammad; Iskandar, Syah; Mahmudi; Muhammad (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This study explores the strategic role of Islamic Religious Education (IRE) in preventing sexual violence within educational institutions. Using a qualitative descriptive approach, the research draws upon interviews with educators, students, and school leaders, supported by analysis of relevant legal and religious documents. Findings indicate that IRE contributes significantly to shaping students' moral consciousness, emphasizing values such as self-respect, social boundaries, and mutual care as taught in Islamic ethics. These values are in line with Indonesia’s Law No. 12 of 2022 on the Crime of Sexual Violence (UU TPKS), highlighting IRE's potential as a legal and moral safeguard. The integration of IRE with a child-protection framework, along with teacher training and the development of context-sensitive learning materials, strengthens its preventive capacity. Moreover, effective prevention demands collaboration between schools, families, communities, and government stakeholders to ensure a safe learning environment. The study concludes that optimizing IRE’s preventive role requires a holistic educational model that is responsive to social issues, grounded in Islamic ethical teachings, and embedded in inclusive curriculum policies. This research contributes to the discourse on value-based education and offers actionable insights for educators and policymakers aiming to combat sexual violence through religious pedagogy. Penelitian ini mengeksplorasi peran strategis Pendidikan Agama Islam (PAI) dalam pencegahan kekerasan seksual di lembaga pendidikan. Dengan pendekatan deskriptif kualitatif, penelitian ini didasarkan pada wawancara dengan pendidik, peserta didik, dan pimpinan sekolah, serta analisis dokumen hukum dan keagamaan yang relevan. Temuan menunjukkan bahwa PAI berkontribusi secara signifikan dalam membentuk kesadaran moral peserta didik, dengan menekankan nilai-nilai seperti penghormatan terhadap diri sendiri, batasan sosial, dan kepedulian terhadap sesama sebagaimana diajarkan dalam etika Islam. Nilai-nilai ini sejalan dengan Undang-Undang No. 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual (UU TPKS), yang menegaskan potensi PAI sebagai perangkat perlindungan moral dan hukum. Integrasi PAI dengan kerangka perlindungan anak, pelatihan guru, serta pengembangan materi ajar yang kontekstual memperkuat kapasitas preventifnya. Lebih lanjut, pencegahan yang efektif membutuhkan kolaborasi antara sekolah, keluarga, masyarakat, dan pemerintah untuk menciptakan lingkungan belajar yang aman. Studi ini menyimpulkan bahwa optimalisasi peran PAI dalam pencegahan kekerasan seksual memerlukan model pendidikan yang holistik, responsif terhadap isu sosial, berlandaskan pada ajaran etika Islam, dan tertuang dalam kebijakan kurikulum yang inklusif. Penelitian ini memberikan kontribusi terhadap diskursus pendidikan berbasis nilai dan menawarkan wawasan aplikatif bagi pendidik dan pembuat kebijakan dalam upaya menanggulangi kekerasan seksual melalui pedagogi keagamaan.